Autosomal-Recessive Hearing Impairment Due to Rare Missense Variants within S1PR2. - Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Ansar, Muhammad; Wang, Xin; Morell, Robert J; Isaacson, Rivka; Belyantseva, Inna A; Dai, Hang; Acharya, Anushree; Qaiser, Tanveer A; et al. (Am J Hum Genet, 2016)
The sphingosine-1-phosphate receptors (S1PRs) are a well-studied class of transmembrane G protein-coupled sphingolipid receptors that mediate multiple cellular processes. However, S1PRs have not been previously reported to be involved in the genetic etiology of human traits. S1PR2 lies within the autosomal-recessive nonsyndromic hearing impairment (ARNSHI) locus DFNB68 on 19p13.2. From exome sequence data we identified two pathogenic S1PR2 variants, c.323G>C (p.Arg108Pro) and c.419A>G (p.Tyr140Cys). Each of these variants co-segregates with congenital profound hearing impairment in consanguineous Pakistani families with maximum LOD scores of 6.4 for family DEM4154 and 3.3 for family PKDF1400. Neither S1PR2 missense variant was reported among ∼120,000 chromosomes in the Exome Aggregation Consortium database, in 76 unrelated Pakistani exomes, or in 720 Pakistani control chromosomes. Both DNA variants affect highly conserved residues of S1PR2 and are predicted to be damaging by multiple bioinformatics tools. Molecular modeling predicts that these variants affect binding of sphingosine-1-phosphate (p.Arg108Pro) and G protein docking (p.Tyr140Cys). In the previously reported S1pr2(-/-) mice, stria vascularis abnormalities, organ of Corti degeneration, and profound hearing loss were observed. Additionally, hair cell defects were seen in both knockout mice and morphant zebrafish. Family PKDF1400 presents with ARNSHI, which is consistent with the lack of gross malformations in S1pr2(-/-) mice, whereas family DEM4154 has lower limb malformations in addition to hearing loss. Our findings suggest the possibility of developing therapies against hair cell damage (e.g., from ototoxic drugs) through targeted stimulation of S1PR2.
Keywords: Amino Acid Sequence; Asian Continental Ancestry Group; Chromosomes, Human, Pair 19; Exome; Genes, Recessive; Hearing Loss; Humans; Lod Score; Logistic Models; Lysophospholipids; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype; Receptors, Lysosphingolipid; Sphingosine

Mutational Spectrum of MYO15A and the Molecular Mechanisms of DFNB3 Human Deafness. - Rehman, Atteeq U; Bird, Jonathan E; Faridi, Rabia; Shahzad, Mohsin; Shah, Sujay; Lee, Kwanghyuk; Khan, Shaheen N; Imtiaz, Ayesha; Ahmed, Zubair M; Riazuddin, Saima; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (Hum Mutat, 2016)
Deafness in humans is a common neurosensory disorder and is genetically heterogeneous. Across diverse ethnic groups, mutations of MYO15A at the DFNB3 locus appear to be the third or fourth most common cause of autosomal-recessive, nonsyndromic deafness. In 49 of the 67 exons of MYO15A, there are currently 192 recessive mutations identified, including 14 novel mutations reported here. These mutations are distributed uniformly across MYO15A with one enigmatic exception; the alternatively spliced giant exon 2, encoding 1,233 residues, has 17 truncating mutations but no convincing deafness-causing missense mutations. MYO15A encodes three distinct isoform classes, one of which is 395 kDa (3,530 residues), the largest member of the myosin superfamily of molecular motors. Studies of Myo15 mouse models that recapitulate DFNB3 revealed two different pathogenic mechanisms of hearing loss. In the inner ear, myosin 15 is necessary both for the development and the long-term maintenance of stereocilia, mechanosensory sound-transducing organelles that extend from the apical surface of hair cells. The goal of this Mutation Update is to provide a comprehensive review of mutations and functions of MYO15A.
Keywords: Alternative Splicing; Animals; Deafness; Disease Models, Animal; Ear, Inner; Exons; Gene Expression Regulation, Developmental; Humans; Mice; Mutation; Myosins; Stereocilia

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

Mutations in TBC1D24, a gene associated with epilepsy, also cause nonsyndromic deafness DFNB86. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Morell, Robert J; Drummond, Meghan C; Ito, Taku; Lee, Kwanghyuk; Khan, Asma A; Basra, Muhammad Asim R; Wasif, Naveed; Ayub, Muhammad; Ali, Rana A; Raza, Syed I; et al. (Am J Hum Genet, 2014)
Inherited deafness is clinically and genetically heterogeneous. We recently mapped DFNB86, a locus associated with nonsyndromic deafness, to chromosome 16p. In this study, whole-exome sequencing was performed with genomic DNA from affected individuals from three large consanguineous families in which markers linked to DFNB86 segregate with profound deafness. Analyses of these data revealed homozygous mutation c.208G>T (p.Asp70Tyr) or c.878G>C (p.Arg293Pro) in TBC1D24 as the underlying cause of deafness in the three families. Sanger sequence analysis of TBC1D24 in an additional large family in which deafness segregates with DFNB86 identified the c.208G>T (p.Asp70Tyr) substitution. These mutations affect TBC1D24 amino acid residues that are conserved in orthologs ranging from fruit fly to human. Neither variant was observed in databases of single-nucleotide variants or in 634 chromosomes from ethnically matched control subjects. TBC1D24 in the mouse inner ear was immunolocalized predominantly to spiral ganglion neurons, indicating that DFNB86 deafness might be an auditory neuropathy spectrum disorder. Previously, six recessive mutations in TBC1D24 were reported to cause seizures (hearing loss was not reported) ranging in severity from epilepsy with otherwise normal development to epileptic encephalopathy resulting in childhood death. Two of our four families in which deafness segregates with mutant alleles of TBC1D24 were available for neurological examination. Cosegregation of epilepsy and deafness was not observed in these two families. Although the causal relationship between genotype and phenotype is not presently understood, our findings, combined with published data, indicate that recessive alleles of TBC1D24 can cause either epilepsy or nonsyndromic deafness.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Chromosomes, Human, Pair 16; Consanguinity; Deafness; Epilepsy; Exome; Exons; Female; Genes, Recessive; Genetic Loci; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA, Messenger; Sequence Analysis, DNA

Perrault syndrome is caused by recessive mutations in CLPP, encoding a mitochondrial ATP-dependent chambered protease. - Jenkinson, Emma M; Rehman, Atteeq U; Walsh, Tom; Clayton-Smith, Jill; Lee, Kwanghyuk; Morell, Robert J; Drummond, Meghan C; Khan, Shaheen N; Naeem, Muhammad Asif; Rauf, Bushra; Billington, Neil; Schultz, Julie M; et al. (Am J Hum Genet, 2013)
Perrault syndrome is a genetically and clinically heterogeneous autosomal-recessive condition characterized by sensorineural hearing loss and ovarian failure. By a combination of linkage analysis, homozygosity mapping, and exome sequencing in three families, we identified mutations in CLPP as the likely cause of this phenotype. In each family, affected individuals were homozygous for a different pathogenic CLPP allele: c.433A>C (p.Thr145Pro), c.440G>C (p.Cys147Ser), or an experimentally demonstrated splice-donor-site mutation, c.270+4A>G. CLPP, a component of a mitochondrial ATP-dependent proteolytic complex, is a highly conserved endopeptidase encoded by CLPP and forms an element of the evolutionarily ancient mitochondrial unfolded-protein response (UPR(mt)) stress signaling pathway. Crystal-structure modeling suggests that both substitutions would alter the structure of the CLPP barrel chamber that captures unfolded proteins and exposes them to proteolysis. Together with the previous identification of mutations in HARS2, encoding mitochondrial histidyl-tRNA synthetase, mutations in CLPP expose dysfunction of mitochondrial protein homeostasis as a cause of Perrault syndrome.
Keywords: Adenosine Triphosphate; Adolescent; Adult; ATP-Dependent Proteases; Endopeptidase Clp; Exome; Female; Genes, Recessive; Gonadal Dysgenesis, 46,XX; Hearing Loss, Sensorineural; Homozygote; Humans; In Situ Hybridization; Male; Mitochondria; Mutation; Pedigree; Phenotype; Young Adult